INTERTEXTUALITY THROUGH BODY LANGUAGE : THE SMILE OF LARBI BEN M’HIDI AND THE YOUTH OF THE PALESTINIAN RESISTANCE. AN ANALYTICAL DESCRIPTIVE SEMIOTIC STUDY - Nassira DJEGHRI ZAROUTA (Ziglôbitha)
Abstract: The concept of intertextuality emerged from the womb of post-structuralism and was realised by semiotics through the research interaction between different currents. The semiotic movement worked to expand its scope, which is no longer restricted to the literary field; its use extended to visual texts and even more so to body language, which can create knowledge accumulations from which subsequent texts can benefit. In its general concept, textualisation is defined as the intersection of a new text with previous texts; knowledge is produced from this legacy through this interconnection, acculturation, influence and impact. The study aims to track the effects of the intertextuality of the smile as an attribute of body language between the smile of a Palestinian youth and the algerian martyr Larbi Ben M’hidi, through a purposive sample between the two individuals to ensure the presence of intertextuality in all its dimensions in order to achieve the objectives of the study. The study reached results, the most important of which is that the smile achieved full and partial intertextuality in all its patterns between the smile of the Palestinian youth and the Algerian martyr Larbi Ben Mehidi, the study confirms the productive nature of intertextuality in body language in achieving interaction and mutual understanding between different people and cultures, especially in achieving historical intertextuality by borrowing from revolutionary symbols. Between the Palestinian Resistance and the Algerian revolution